2023
DOI: 10.3389/fbioe.2022.1098973
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional-printed porous prosthesis for the joint-sparing reconstruction of the proximal humeral tumorous defect

Abstract: Background: Tumorous bone defect reconstructions of the proximal humerus with joint sparing is a challenge. Numerous reconstruction methods have been proposed but the proximal residual humerus is commonly sacrificed because of its extremely short length. To preserve the proximal humerus and improve clinical outcomes, we designed a three-dimensional (3D) printed uncemented prosthesis with a porous structure to treat tumorous bone defects of the proximal humerus.Methods: Our analysis included seven patients trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Three‐dimensional‐printed custom‐made implants provide an appealing reconstruction technique for limb or joint salvage surgeries. Promising functional outcomes using this technique have been reported in tibial, femoral, and humeral defect reconstruction 3,5,6,8,14,15 . Additionally, the radiographic evaluation revealed that the porous interface favored bone ingrowth for prolonged fixation 16 .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Three‐dimensional‐printed custom‐made implants provide an appealing reconstruction technique for limb or joint salvage surgeries. Promising functional outcomes using this technique have been reported in tibial, femoral, and humeral defect reconstruction 3,5,6,8,14,15 . Additionally, the radiographic evaluation revealed that the porous interface favored bone ingrowth for prolonged fixation 16 .…”
Section: Discussionmentioning
confidence: 92%
“…Promising functional outcomes using this technique have been reported in tibial, femoral, and humeral defect reconstruction. 3,5,6,8,14,15 Additionally, the radiographic evaluation revealed that the porous interface favored bone ingrowth for prolonged fixation. 16 However, one of the concerns associated with 3D-printed custommade implants is mechanical properties.…”
Section: Discussionmentioning
confidence: 99%
“…(Fig. 6 A-D) iv) Effective Osseointegration: Effective osseointegration at the prosthesis-bone interface is a vital condition for long-term prosthesis survival [ 32 , 36 , 57 , 58 ]. We incorporated a porous structure mimicking trabecular bone at the interface where the prosthesis contacts the bone.…”
Section: Discussionmentioning
confidence: 99%